Type II syndactyly or synpolydactyly. - Merlob, P (1986)
A new family with syndactyly type II or synpolydactyly is described with 16 affected members in six generations. No other major skeletal or extraskeletal malformations were present, but the association with minor local anomalies may be a common feature. Various metacarpal or metatarsal abnormalities may be part of this type of syndactyly. The family pedigree confirms the autosomal dominant mode of inheritance with incomplete penetrance and the frequent occurrence of non-manifesting heterozygotes resulting in 'skipped generations'.